Assessment of Financial Literacy among Women In Machhapuchhre Rural Municipality Of Kaski District (Samriddhi Journal of Development Studies, 2024)
This study assesses the level of financial literacy among women in Machhapuchhre Rural Municipality (MRM), Kaski District. It aims to understand their financial knowledge, attitudes, behaviors, and the socio-demographic factors influencing these components. A descriptive and explanatory design was employed. Structured questionnaires were administered to 236 women selected purposively from all nine wards of MRM. The study analyzed data using descriptive statistics, cross-tabulation, correlation, and regression through SPSS. The study revealed a moderate understanding of savings and financial institutions among women. However, their practical application of financial knowledge was limited. Education was found to influence financial knowledge positively, while age negatively influenced financial attitude. A significant barrier to financial literacy was a lack of awareness, exposure, and trust in financial institutions. Financial literacy among women in MRM is shaped by socio-demographic and psychological factors. The study challenges the assumption that higher education guarantees better financial literacy, highlighting the need for targeted practical financial education and awareness programs. The study proposes targeted financial education workshops, increased use of digital tools, and strategic partnerships with cooperatives and women’s groups.